Stanowisko Parlamentu Europejskiego wobec pomocy humanitarnej - Kaczmarek, Filip (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
Unia Europejska wraz z państwami członkowskim tej organizacji jest największym dawcą pomocy humanitarnej na świecie. Parlament Europejski jest jedną z kluczowych instytucji UE i jedyną spośród nich, wyłanianą w wyniku wyborów bezpośrednich. Celem tekstu jest zbadanie stanowiska Parlamentu wobec pomocy humanitarnej, począwszy od przyjęcia Konsensusu europejskiego w sprawie pomocy humanitarnej w 2007 r. do końca czerwca 2018 r. Metodą badawczą jest analiza różnych form działalności Parlamentu w badanym zakresie. Jedną z konkluzji jest zdefiniowanie dylematu Parlamentu, polegającego na próbie pogodzenia zasad pomocy humanitarnej i partykularnych interesów państw członkowskich UE.

The European Union, together with the Member States of this organisation, is the largest donor of humanitarian aid in the world. The European Parliament is one of the EU’s key institutions and the only one of them to be directly elected. The aim of the peper is to examine Parliament’s position on humanitarian aid, from the adoption of the European Consensus on Humanitarian Aid in 2007 to the end of June 2018. The research method is an analysis of the various forms of Parliament’s activity in the field under examination. One of the conclusions is to define Parliament’s dilemma of trying to reconcile the principles of humanitarian aid with the particular interests of EU Member States.
The European Parliament’s position on humanitarian aid
Keywords: pomoc humanitarna; Parlament Europejski; Unia Europejska; konsensus; Humanitarian aid; European Parliament; European Union; Consensus